The Evaluation Of Airline Service Quality Using The Analytic Hierarchy Process. - Mustafa, Adli; Fong, Jia-Pei; Lim, Siaw-Peng; Abd Hamid, Hamidah (2005)
This paper presents an application of the analytical hierarchy process (AHP) to determine service quality of airlines.